2013
DOI: 10.1371/journal.pone.0084787
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Correlates of Musth in Free-Ranging Asian Elephants (Elephas maximus) Determined by Non-Invasive Faecal Steroid Hormone Metabolite Measurements

Abstract: The occurrence of musth, a period of elevated levels of androgens and heightened sexual activity, has been well documented for the male Asian elephant (Elephas maximus). However, the relationship between androgen-dependent musth and adrenocortical function in this species is unclear. The current study is the first assessment of testicular and adrenocortical function in free-ranging male Asian elephants by measuring levels of testosterone (androgen) and cortisol (glucocorticoid – a physiological indicator of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
(77 reference statements)
2
18
0
Order By: Relevance
“…A similar finding was presented in a recent study on giraffes, where the oldest bulls also showed significantly higher fAM levels, when sexually active (Seeber et al, 2013). For a number of species, times of sexual activity are often correlated with elevated androgen levels, as for example shown in bison (Mooring et al, 2004) or African and Asian elephant (Ganswindt et al, 2005;Ghosal et al, 2013), with already minor changes in fAM levels being related to male sexual activity in elephants (Rasmussen et al, 2008). In contrast, elephant bulls in musth show much higher androgen levels than necessary to stimulate sexual behavior and therefore appear more likely to be linked to intra-sexual competition and mate guarding (Rasmussen et al, 2008).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar finding was presented in a recent study on giraffes, where the oldest bulls also showed significantly higher fAM levels, when sexually active (Seeber et al, 2013). For a number of species, times of sexual activity are often correlated with elevated androgen levels, as for example shown in bison (Mooring et al, 2004) or African and Asian elephant (Ganswindt et al, 2005;Ghosal et al, 2013), with already minor changes in fAM levels being related to male sexual activity in elephants (Rasmussen et al, 2008). In contrast, elephant bulls in musth show much higher androgen levels than necessary to stimulate sexual behavior and therefore appear more likely to be linked to intra-sexual competition and mate guarding (Rasmussen et al, 2008).…”
Section: Discussionsupporting
confidence: 85%
“…Such alterations in androgen levels have even been described in non-seasonally breeding species such as chimpanzee (Pan troglodytes schweinfurthii), with males showing elevated androgen levels when parous females are present and therefore male-male aggression increases (Muehlenbein et al, 2004;Muller and Wrangham, 2004). Furthermore, a temporal increase in aggression related to male 4 reproductive activity appears to be androgen mediated in African (Loxodonta africana) and Asian elephants (Elephas maximus) (Ganswindt et al, 2005;Ghosal et al, 2013;Rasmussen et al, 2008).…”
Section: Introductionmentioning
confidence: 90%
“…We used the protocol described in Ganswindt et al (2003) for African elephants, which has been successfully validated for Asian elephants (Ghosal et al, 2013;Pokharel et al, 2017), to extract steroid and analyse the fGCM levels. The faecal extraction and analysis for measuring immunoreactive fGCM (lg g À1 ) have been explained in detail in Pokharel et al (2017).…”
Section: Steroid Analysesmentioning
confidence: 99%
“…The results of our radiometabolism studies confirmed that the epi-A EIA detected immunoreactive, radiolabelled fTM in both an adult male and female. EIAs using antibodies directed against epi-A have also been validated for monitoring the gonadal status of other mammals, including the African and Asian elephant, Loxodonta africana and Elephas maximus [ 58 , 59 ] and the sun bear, Helarctos malayanus [ 60 ]. Epi-A is also a major testosterone metabolite in faeces of macaques [ 19 , 61 ].…”
Section: Discussionmentioning
confidence: 99%